2022
DOI: 10.1075/prag.18.1.04hou
|View full text |Cite
|
Sign up to set email alerts
|

News production theory and practice

Abstract: This paper considers notions of agency, interaction and power in business news journalism. In the first part, we present a bird’s eye view of news access theory as it is reflected in selected sociological and anthropological literature on the ethnography of news production. Next, we show how these theoretical notions can be applied to the study of press releases and particularly to the linguistic pragmatic analysis of the specific social and textual practices that surround their transformation into news report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This is part of a recent change in research focus towards discursive practices taking place in the news production process (Catenaccio et al, 2010;Clayman and Reisner, 1998;Cotter, 2010;Jacobs et al, 2008;Perrin, 2006Perrin, , 2010Peterson, 2001Peterson, , 2003Van Hout and Jacobs, 2008;Van Hout and Van Praet, 2011).…”
Section: A Linguistic Approach To Journalism Practicementioning
confidence: 97%
See 1 more Smart Citation
“…This is part of a recent change in research focus towards discursive practices taking place in the news production process (Catenaccio et al, 2010;Clayman and Reisner, 1998;Cotter, 2010;Jacobs et al, 2008;Perrin, 2006Perrin, , 2010Peterson, 2001Peterson, , 2003Van Hout and Jacobs, 2008;Van Hout and Van Praet, 2011).…”
Section: A Linguistic Approach To Journalism Practicementioning
confidence: 97%
“…These newsroom meetings provide a forum for introducing, reviewing, negotiating, selecting, following up on and assigning ideas for news stories for the next day's paper (Clayman and Reisner, 1998;Cotter, 2010;Van Hout and Jacobs, 2008). Thus, the newsroom meeting is a setting for decision-making leading to inclusion and exclusion of ideas for new news stories and thereby it performs a gate-keeping function (Golding and Elliott, 1979).…”
Section: Introduction: Newsroom Meetings As Loci For Cultural (Re)promentioning
confidence: 96%
“…These consist not only of press releases but also include personal relationships and other more subtle contacts between the two parties. As PR professionals want to present their information subsidies as original journalistic content that serves the public interest instead of a form of free advertising in favor of specific private interests, we can state that source efforts are more successful when information subsidies are presented as the result of independent journalistic news gathering and production (Davies 2008; Davis 2000; Van Hout and Jacobs 2008). Reich (2010), for instance, found that PR practitioners are identified as information sources in no more than 11 percent of the observed cases as their presence in the news is mostly covered in what he calls a “smokescreen of anonymity” (p. 811).…”
Section: International Ngos: the New(s) Kids On The Block?mentioning
confidence: 99%
“…This level of detail can show the construction of the story both in the writing but in the handling of the social situations in the newsroom. Van Hout and Jacobs also utilise key stroke technology to look at how a story is identified and developed as well as participant observation and interviews -following Peterson's (2001) idea of news, moving away from structures to a more contingent, 'interpretive practice' (Van Hout and Jacobs, 2008). Peterson himself attempts to capture a different area of discourse -that of spoken contact with sources.…”
Section: Journalism As a Discursive Practicementioning
confidence: 99%